Geochemistry and grain size distribution of surface sediments of a large semi-enclosed lagoon connected to the western Bay of Bengal. (5th January 2019) - Adikaram, Madurya; Pitawala, Amarasooriya; Ishiga, Hiroaki; Jayawardana, Daham
Abstract: Batticaloa is a large (135.5 km 2 ), semi-enclosed, micro-tidal lagoon that formed by barrier deposits in eastern Sri Lanka and has a unique geographic position due to its tropical monsoonal climate and absence of tectonics. The recent soft bottom sediments of Batticaloa lagoon were studied on the basis of geochemistry and grain size distribution in order to interpret their characteristics and provenance. Poor to moderately sorted medium sands are the dominant sedimentary deposits for the lagoon; therefore, a medium energy condition is suggested for sediment deposition. The average silt and clay fraction of the lagoon sediments is less than 3%, indicating medium or high energy flows. Coarser deposits are restricted to channel and lagoon mouths. The scatter plots of Nb, Zr, Cr and Sc vs. Th and Cr/V vs. Y/Ni show a felsic provenance for the sediments. The normalized diagrams of major element oxides and trace elements for the regional rocks (Vijayan Complex of Sri Lanka) indicate high country rock influence for the sedimentation for the semi-enclosed setting. The enrichment and distribution of Zr, Th, Nb, Cr and TiO2 suggest the possibility of mineral sands that are fractionated with hydrodynamic setting of the lagoon.